1999
DOI: 10.1006/abbi.1998.1097
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Acidic Residues to the Conformational Stability of Common-Type Acylphosphatase

Abstract: Common-type acylphosphatase is a small cytosolic enzyme whose catalytic properties and three-dimensional structure are known in detail. All the acidic residues of the enzyme have been replaced by noncharged residues in order to assess their contributions to the conformational stability of acylphosphatase. The enzymatic activity parameters and the conformational free energy of each mutant were determined by enzymatic activity assays and chemically induced unfolding, respectively. Some mutants exhibit very simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
(42 reference statements)
1
2
0
Order By: Relevance
“…It has been previously suggested that enzymatic activity can be used as a probe for the assessment of the native-like structure of an AcP protein variant, provided that the mutated residue does not participate to the catalytic mechanism and/or does not contribute to the formation of the active site (26). The activity measurements performed here clearly show that all these AcP variants maintain a native-like structural architecture.…”
Section: Resultssupporting
confidence: 52%
“…It has been previously suggested that enzymatic activity can be used as a probe for the assessment of the native-like structure of an AcP protein variant, provided that the mutated residue does not participate to the catalytic mechanism and/or does not contribute to the formation of the active site (26). The activity measurements performed here clearly show that all these AcP variants maintain a native-like structural architecture.…”
Section: Resultssupporting
confidence: 52%
“…The protein engineering method to study the mutation effects on AcP unfolding and aggregation has been actively applied to describe amyloid fibril formation as well as protein structure–function relationships. ,, Dobson and co-workers have systematically reported the effects of single point mutations of AcP and found that V9A, E29D, A30G, S87T, and S92T mutations showed increased aggregation rate, whereas V20A, G34A, V39A, L89A, Y91Q, and Y98Q mutations displayed the opposite result. ,, Among those mutations, A30G accelerates and Y91Q decelerates the aggregation rate most distinctively. ,, On the other hand, both of those mutations contribute to slow down the folding rate of AcP with respect to the wild type. , Despite the extensive mutation experiments on AcP protein, the molecular origin and the structural motifs to promote the aggregation and folding rate changes have not been rationalized at the atomic-level due to the absence of the AcP mutant structures. Flöck et al have previously performed the molecular dynamics (MD) simulations for AcP monomer of its wild type under 25% (v/v) trifluoroethanol (TFE)/water solvent and found the enhancement of aggregation propensity mainly due to the TFE and β-propensity of the α1-helix (residues 22–33) .…”
Section: Introductionmentioning
confidence: 99%
“…Hu-CT [21] 841 ± 156 5.0-6.0 0.15 ± 0.01 0.59 ± 0.04 5610 ± 670 Hu-MT [22] 1224 ± 120 4.8-5.8 0.34 ± 0.03 0.75 ± 0.08 3420 ± 500 AcPDro [7] 35 ± 3 5. Table 2.…”
Section: Resultsmentioning
confidence: 99%